Strategi Marketing Jamu Zona N’Deso Melalui Media Sosial untuk Memperluas Cakupan Pemasaran Produk Jamu Zona N’Deso - Hidayat, Ridho Hattabul; Shafardan, M. Daffa; Fatah, Angger Praba; Putra, Bintang Anugrah; Saputri, Andini Rahma; Arahman, Anissa; Widyaputri, Afrinda Tirta; Cahyaningtyas, Ayu; Harimurti, , Sabtanti (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2024)
This community service activity is expected to help increase community knowledge about MSME development in Padukuhan Semoyo so that it can help improve the community's economy. One of the problems of MSMEs in Padukan Semoyo is a lack of understanding about online product marketing. the method carried out is in the form of FGDs with MSME owners as a systematic approach to conveying information and learning materials. This MSME FGD was held at one of the houses of a resident of Padukuhan Semoyo as the owner of the Jamu Zona N’Deso MSME, this activity was carried out on January 22, 2024 with 2 participants. then, after conducting FGDs, video taking and taking photos of Jamu Zona N’Deso products were carried out, these activities were carried out on February 05, 2024 and February 09, 2024. based on the results of the activities carried out by MSME owners, it is hoped that they can add new insights into the digitization of MSMEs and can bring new innovations to the development of MSMEs in Padukuhan Semoyo.